2021
DOI: 10.1371/journal.pone.0245209
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin as a potential treatment for COVID-19-induced acute kidney injury: Based on network pharmacology and molecular docking study

Abstract: Kidneys are one of the targets for SARS-CoV-2, it is reported that up to 36% of patients with SARS-CoV-2 infection would develop into acute kidney injury (AKI). AKI is associated with high mortality in the clinical setting and contributes to the transition of AKI to chronic kidney disease (CKD). Up to date, the underlying mechanisms are obscure and there is no effective and specific treatment for COVID-19-induced AKI. In the present study, we investigated the mechanisms and interactions between Quercetin and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 56 publications
0
33
0
Order By: Relevance
“…For example, D + Q resulted in a reduction in SASP-associated pro-inflammatory cytokines during idiopathic pulmonary fibrosis, an age-related lung disease 180 , and a recent study showed that fisetin and D + Q reduced SASP and improved survival in a mouse model of β-coronavirus 84 . Quercetin may also have beneficial renal-protective and senolyticindependent effects during SARS-CoV-2 infection 181 . However, more work is needed to determine whether senolytics could be a viable option in humans to rejuvenate an aged immune system as either a preventative measure before SARS-CoV-2 infection or as a treatment option during acute infection.…”
Section: Senolyticsmentioning
confidence: 99%
“…For example, D + Q resulted in a reduction in SASP-associated pro-inflammatory cytokines during idiopathic pulmonary fibrosis, an age-related lung disease 180 , and a recent study showed that fisetin and D + Q reduced SASP and improved survival in a mouse model of β-coronavirus 84 . Quercetin may also have beneficial renal-protective and senolyticindependent effects during SARS-CoV-2 infection 181 . However, more work is needed to determine whether senolytics could be a viable option in humans to rejuvenate an aged immune system as either a preventative measure before SARS-CoV-2 infection or as a treatment option during acute infection.…”
Section: Senolyticsmentioning
confidence: 99%
“…Wang et al considered that quercetin can protect AKI by inhibiting ferroptosis [ 38 ]. Also, Gu et al found that quercetin may be a promising therapeutic avenue for SARS-CoV-2 injury-induced AKI [ 39 ]. Scutellarein is a flavonoid monomer that has been demonstrated to exert various pharmacological effects including anticancer [ 40 ], anti-inflammatory [ 41 ], and antifibrosis activities [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to protecting lung tissue, XBJI reduces the levels of serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST), downregulates the expression of TNF-α and IL-6, upregulates the expression of IL-10 and SOCS1, and reduces liver injury caused by inflammation in rats ( Li et al, 2016 ). Quercetin regulates apoptosis-related signaling pathways, blocks the inflammatory response, and protects against SARS-COV-2-induced acute kidney injury ( Gu et al, 2021 ). Dysosmia is a common symptom in COVID-19 patients ( Tong et al, 2020 ).…”
Section: Research Status Of Antiviral Tcmsmentioning
confidence: 99%